Frequently Asked Questions About Tanning and Skin Care - Brezina, Corona (New York, NY : Rosen Pub., 2010)
Describes the effects of tanning on the skin and body, including the potential dangers and long-term effects of tanning, and explains the importance of proper skin care.
Why is tanning so popular? -- What are some typical tanning practices? -- How does tanning affect the skin? -- What are the long-term effects of tanning? -- What do doctors say about tanning?
Includes bibliographical references (p. 60-61) and index.
Keywords: Skin -- Care; Skin cancer -- Prevention